Application of Smoke Washer Device in Waste Incineration Machine to Reduce Exhaust Gas Emissions at Jatibarang Landfill Semarang - Supraptono, Eko; Kurniawan, Galang Wahid; Sutopo, Yeri; Khumaedi, Muhammmad; Irfan, Mohamad; Sonhaji, Sonhaji; Hidayattullah, Ardhana Luthfi; Tukiman, Tukiman (Jurnal Abdimas, 2025)
Waste management at the Jatibarang Landfill, Semarang, faces challenges due to incinerator exhaust gas emissions, potentially decreasing air quality, and posing health risks to surrounding communities. This community service program implemented a smoke washer (wet scrubber) adapted to the conditions of a simple incinerator. The activities included designing and fabricating the device, integrating electrical and control systems, providing operational training for partners (CV Dewa Nata Persada and Jatibarang Landfill), and conducting field testing of exhaust gas quality. The tested parameters consisted of particulate matter (PM), carbon monoxide (CO), and sulfur dioxide (SO₂), which were compared with the quality standards of the Ministry of Environment and Forestry Regulation No. P.70 of 2016. The measurement results indicated that all parameters were below the threshold limits, with pollutant concentrations decreasing from the initial operation to the following hours, signifying more stable performance of the device under steady-state operating conditions. These findings demonstrate the importance of the community service program in enhancing partners’ awareness and capacity in environmentally friendly waste management, underscoring the project's significant impact.